Divergent effects of type-I interferons on regulatory T cells. Issue 2 (April 2015) - Piconese, Silvia; Pacella, Ilenia; Timperi, Eleonora; Barnaba, Vincenzo
Highlights Conflicting data exist about type-I IFNs playing pro- or anti-Treg activities. IFNs may induce alternative suppressor T cells such as Tr1 and FoxA1+ Treg. Some IRFs regulate Treg functions, even if the link with IFN response is unclear. IFN therapy may reduce Treg in the short term but expand Treg in the long term.